2006
DOI: 10.1186/1477-7525-4-94
|View full text |Cite
|
Sign up to set email alerts
|

Combining scores from different patient reported outcome measures in meta-analyses: when is it justified?

Abstract: Background: Combining outcomes and the use of standardized effect measures such as effect size and standardized response mean across instruments allows more comprehensive meta-analyses and should avoid selection bias. However, such analysis ideally requires that the instruments correlate strongly and that the underlying assumption of similar responsiveness is fulfilled. The aim of the study was to assess the correlation between two widely used health-related quality of life instruments for patients with chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 26 publications
0
60
0
1
Order By: Relevance
“…This heterogeneity hindered assessment of the impact of the interventions [54,55]. The majority of studies assessed outcomes from more than one aspect of health care (process, outcomes, and satisfaction with care) without taking multiple comparisons into account [56,57].…”
Section: Resultsmentioning
confidence: 99%
“…This heterogeneity hindered assessment of the impact of the interventions [54,55]. The majority of studies assessed outcomes from more than one aspect of health care (process, outcomes, and satisfaction with care) without taking multiple comparisons into account [56,57].…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] Given the range of different scales to measure OHRQoL, each with different scoring methods and scoring ranges, any synthesis of data is challenging; different scales may be combined for meta-analysis provided that scales measure similar constructs and that researchers are mindful of the increased risk of heterogeneity. [32][33][34][35] The purpose of this systematic review was to assess the impact of treatment with ISCs, IFDPs, IRDPs, RPDs, and TFDPs on quantifiable measures of OHRQoL in patients with partial edentulism. The following research question was posed: "What is the effect of different dental prosthetic interventions for replacing missing teeth in partially dentate patients with respect to the changes in oral health-related quality of life?"…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors of the previous systematic review included multiple measures of global well-being [7], an approach that may be problematic given that recent research has suggested that the pooling of global well-being instruments could result in biased meta-analyses [20]. More specifically, the use of different instruments to assess global well-being might attenuate any estimated effects or add spurious between-study variance because of between-measure "noise."…”
Section: Introductionmentioning
confidence: 99%